Doppler spectrum of scatterng of pulsed focused wave beams by axial-symmetric flows - Barannik, E.A.; Skresanova, I.V. (Biophysical Bulletin, 2005)
On the basis of the known solution for the pulsed Doppler flow-line spectrum, it is derived the general analytical expressions for the full Doppler spectra formed by axial-symmetric flows at the scattering of focused wave beams at pulsed mode. In the particular case of the poiseile flow a formula of proportionality between the average speed of the blood flow and the average frequency of the Doppler spectrum was discovered. The found form allows us to increase the accuracy of diagnostically important parameters of blood flow.